The Self Regulation in Online Gambling Platforms : Marketing strategies and social responsibility to the young people - Galmes-Cerezo, María; Maestro-Espínola, Lidia; Carcelén-García, Sonia (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
With the expansion of online gambling, stakeholders are looking for ways to minimise the risk to young people, who are particularly vulnerable. The multi-case study, which analyses the web platforms of six gambling operators, finds that all include responsible gambling microsites and applications. The multi-case study, which analyses the web platforms of six gambling online operators, finds that all include responsible gaming microsites and applications, which have significant differences in the quality of the responsible gaming experience of young people. Operators' self-regulation is improving the online experience of responsible gambling, but some of their marketing strategies continue to encourage risky gambling behaviour among young people.